Design Thinking Method to Develop a Digital Evidence Handling Management Application - Erika Ramadhani; Amrullah Sidiq (Khazanah Informatika, 2022)
Handling digital evidence in forensics is a very crucial task. Incorrect handling can cause the evidence to become invalid as proof of a crime in court. The procedure of handling digital evidence, starting from its collection, usage, and storage, affects its acceptability in the judicial process. Therefore, a digital evidence management system becomes imperative for police researchers and investigators. This study aims at designing such a system using the design thinking method, which goes through five stages: empathy, definition, idea, prototype, and test. The result of the study is a web-based system prototype. The prototype user testing attains a system usability scale (SUS) value of 60. The SUS value means that the prototype is in the category of marginal low and indicates that the prototype does not meet the feasibility and needs improvement.